Customer Relationship Marketing: Role of Artificial Intelligence, Blockchain Technology, and Regulatory Environment in Telecom Sector of Pakistan: https://doi.org/10.55966/assaj.2025.4.1.061 - Waseem Mushtaq Khan; Abdullah Farooq; Ali Haider; Mujahid ullah (`, 2025)
Consumer Relationship Marketing (CRM) is a critical strategy in the telecom sector, aiming to enhance customer engagement, trust, and long-term retention. The integration of artificial intelligence (AI) and Blockchain technology has revolutionized CRM by enabling data-driven decision making, personalized customer interactions, and secure data management this study examines the role of AI ,Blockchain, and regulatory environment in shaping CRM Practices in Pakistan telecom industry. AI driven tools such as predictive analytics, Chabot’s, and sentiment analysis enhance customer experiences, while blockchain ensures data security, transparency, and trust .However, the adoption of these technologies faces challenges, including high implementation costs, regulatory constraints, and a lack of technical expertise. The regulatory environment governed by the Pakistan telecommunication authority (PTA), plays a crucial role in defining data privacy policies and compliance measures, impacting how telecom firm integrate AI and Blockchain in their CRM strategies. This study highlights the need for a balanced approach where telecom companies align technological innovation with regulatory requirements to optimize customer relationship management.it includes that effective collaboration between policymakers and telecom operators is essential for fostering and ecosystem that encourages innovation while ensuring consumer protection and regulatory compliance. Keywords: Customer Relation Marketing, Artificial Intelligence, Block Chain Technology